Attitudinal Change in Elderly Citizens Toward Social Robots: The Role of Personality Traits and Beliefs About Robot Functionality - Damholdt, Malene F.; Nørskov, Marco; Yamazaki, Ryuji; Hakli, Raul; Hansen, Catharina Vesterager; Vestergaard, Christina; Seibt, Johanna (Frontiers in Psychology, 2015)
Attitudes towards robots influence the tendency to accept or reject robotic devices. Thus it is important to investigate whether and how attitudes towards robots can change. In this pilot study we investigate attitudinal changes in elderly citizens toward a tele-operated robot in relation to three parameters: (i) the information provided about robot functionality, (ii) the number of encounters, (iii) personality type. Fourteen elderly residents at a rehabilitation centre participated. Pre-encounter attitudes towards robots, anthropomorphic thinking, and personality were assessed. Thereafter the participants interacted with a tele-operated robot (Telenoid) during their lunch (c. 30 min.) for up to three days. Half of the participants were informed that the robot was tele-operated (IC) whilst the other half were naïve to its functioning (UC). Post-encounter assessments of attitudes towards robots and anthropomorphic thinking were undertaken to assess change. Attitudes towards robots were assessed with a new generic 35-item questionnaire (Attitudes towards social robots scale: ASOR-5), offering a differentiated conceptualization of the conditions for social interaction. There was no significant difference between the IC and UC groups in attitude change towards robots though trends were observed. Personality was correlated with some tendencies for attitude changes; Extraversion correlated with positive attitude changes to intimate-personal relatedness with the robot (r=.619) and to psychological relatedness (r=.581) whilst Neuroticism correlated negatively (r=-.582) with mental relatedness with the robot. The results tentatively suggest that neither information about functionality nor direct repeated encounters are pivotal in changing attitudes towards robots in elderly citizens. This may reflect a cognitive congruence bias where the robot is experienced in congruence with initial attitudes, or it may support action-based explanations of cognitive dissonance reductions, given that robots, unlike computers, are not yet perceived as action targets. Specific personality traits may be indicators of attitude change relating to specific domains of social interaction. Implications and future directions are discussed.